The Magnitude Effect on Tactile Spatial Representation: The Spatial–Tactile Association for Response Code (STARC) Effect - Bollini, Alice; Campus, Claudio; Esposito, Davide; Gori, Monica (Frontiers in Neuroscience, 2020)
The human brain uses perceptual information to create a correct representation of the external world. Converging data indicate that the perceptual processing of time, space, and quantities frequently is based on a shared mental magnitude system, where low and high quantities are represented in the left and right space, respectively. The present study explores how the mental magnitude system affects spatial representation in the tactile modality. We investigated these processes using Stimulus-Response Compatibility (S-R) tasks. In our study, the participant performed a discrimination task between high and low-frequency vibrotactile stimuli, regardless of the stimulation’s spatial position. When the response code was incompatible with the mental magnitude line (i.e., left button for high frequency and right button for low-frequency responses), we found that the participants bypassed the spatial congruence, showing a magnitude S-R compatibility effect. We called this phenomenon the Spatial–Tactile Association of Response Codes (STARC) effect. Moreover, we observed that the internal frame of reference embodies the STARC effect. Indeed, the participants’ performance reversed between uncrossed and crossed-hands posture, suggesting that spatial reference frames play a role in the process of expressing mental magnitude, at least in terms of the tactile modality.